KEBUTUHAN ARMADA DAN KESESUAIAN TARIF TAKSI KONVENSIONAL DI KOTA MATARAM BERDASARKAN BOK, ATP DAN WTP - I WAYAN SUTEJA; HASYIM HASYIM; I GEDE PUTU WARKA (Universitas Mahasaraswati Mataram, 2019)
With the development of technology, the thinking to use applications in the business world also develops. One of them is a business in the field of transportation. At present an application-based transport service has emerged. The emergence of these services, the Conventional Taxis have new competitors. The existence of such competition has led to disputes between conventional taxis and application-based taxis. The existence of Application-Based Taxi, causing some people in the city of Mataram have the opportunity to switch interests using Application-Based Taxi. Under these conditions, the number of fleets and the suitability of conventional taxi rates in the city of Mataram need to be reviewed. In this study, examined taxi rates according to the calculation of vehicle operating costs. Then compared with the ability to pay and the will of the people of the City of Mataram. Then the number of taxi fleet requirements for the City of Mataram will be calculated. From the results of this study it can be concluded that: 1). there is an excess number of taxi fleets, which is 550 fleet optically, but in reality the current taxi fleet operating based on real conditions in the field is as many as 636 fleets from all operators, 2). 48.75% of respondents have the ability to pay a tariff of Rp.3,900 / kilometer and the remaining 52.25% of respondents are forced to use conventional taxis, 3). Current rates are in accordance with government regulations. This can be seen from the calculation of vehicle operating costs (BOK) for the tariff per kilometer is Rp. 4,000 per kilometer while the current tariff is Rp. 3,900, - only a difference of Rp. 100